Pelatihan Tahfizh Menggunakan Metode Qiroati di Pondok Tahfizh Insan Cendikia Taratak Kec. Pesisir Selatan - Rahmah, Hafizhatur; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2023)
This training for the community is a general service, and the focus of this service is the students of Pondok tahfizh insan cendikia Taratak subdistrict. South Coast. This training takes the form of reading the Koran well and correctly using the qiroati method and Tajwid Science Rules. In the implementation of popularizing the Koran, various methods have emerged which are quite helpful in making the process of learning to read the Koran well and correctly easier. The method used in this community service uses Participatory Action Research (PAR), this (PAR) approach is because the actions are carried out not only to obtain the truth, but also to create the desired conditions. The implementation of the qiroati method is carried out by direct practice using the Alquran as media. In the activities carried out using the qiroati method for the students of pondok tahfizh insan cendikia Taratak sub-district. In Pesisir Selatan there are several social impacts obtained, including: 1) Islamic boarding school students can receive learning to read the Koran using the qiroati method. 2) Some of the Islamic boarding school students can improve their reading of the Koran. However, there are also some students who have not been able to improve the quality of their reading. 3) Teachers receive counseling to teach reading the Koran using the qiroati method to Islamic boarding school students, and increase their insight on how to teach the Koran using the qiroati method. 4) As the activity progresses, the number of students taking part in the activity increases.